Prevalence of c-myc expression in breast lesions associated with microcalcifications detected by routine mammography - Mazzini, Renato Coimbra (2009)
CONTEXT AND OBJECTIVE: Genetic abnormalities in cell proliferation-regulating genes have been described in premalignant lesions. The aims here were to evaluate c-myc protein expression in non-palpable breast lesions associated with microcalcifications, detected by screening mammography, and to compare these results with histopathological, clinical and epidemiological variables. DESIGN AND SETTING: Analytical cross-sectional study, with retrospective data collection, in a university hospital in São Paulo. METHODS: Seventy-nine female patients who underwent routine mammography between 1998 and 2004 were studied. Lesions classified by the Breast Imaging Reporting and Data System (BI-RADS) as 4 or 5 underwent percutaneous biopsy using a large-core needle. Ninety-eight lesions were studied anatomopathologically. Paraffin blocks properly representing the lesions were selected for immunohistochemical analyses using the streptavidin-biotinperoxidase technique with monoclonal mouse c-myc antibodies. RESULTS: Among the 98 lesions, 29 (29.6%) contained malignant neoplasia; 40 (40.8%) had a positive immunohistochemical reaction for c-myc. When the groups were divided between lesions without atypias versus atypical lesions plus malignant lesions, 31.03% of the 58 lesions without atypias were positive for c-myc and 55% of the 40 malignant and atypical lesions (P = 0.018). Comparing the atypical lesions with ductal carcinoma in situ versus the benign lesions without atypias, c-myc was present in 51.61% of the 31 atypical lesions and 31.03% of the benign lesions without atypias (P = 0.057). CONCLUSION: C-myc protein was more frequently expressed in atypical and malignant lesions than in benign lesions without atypias. C-myc expression correlated with the presence of atypias (P = 0.018).